THE ARCHETYPES IN THE MAIN CHARACTER OF JOE GOLDBERG IN THE NOVEL YOU - Grace, Sophie; Nitisari, Dwi (Universitas Gunadarma, 2022)
The problem of this reseach is what are the types of archetypes found in Joe Goldberg as the main character in the novel titled YOU meanwhile the purpose of this research is to find out the types of archetypes which are found in the main character namely Joe Goldberg used the theory of collective unconscious by Carl Jung. This research used qualitative method in analyzing the data because it consists of words, pharases, and clauses not in numbers. The result of this research showed after the researchers classifying forty three data which are taken from novel, it is found three of eight archetypes namely thirty three data of Persona, nine data of Shadow, and one datumof Hero that appear in the main character of Joe Goldberg.